The Influence of International Human Rights Instruments on Domestic Legislation: A Comparative Study of Four Countries - Joupy G.Z Mambu; Novita Marven Mongdong (Eastasouth Institute, 2023)
The purpose of this study is to give a comparative analysis of how these countries' legal systems, policies, and practices treat and implement international human rights norms. The methodology of this research utilizes a comparative research design, which combines primary and secondary data collection methods. Primary data was collected through semi-structured interviews with key stakeholders involved in human rights legislation, including government officials, legislators, human rights organizations, legal experts, and academics. This research contributes to the existing literature on human rights legislation in Southeast Asia by providing a comprehensive comparative analysis of the influence of international human rights instruments on domestic legislation. Its findings provide insights into the challenges and opportunities in incorporating human rights standards into domestic law and provide recommendations for strengthening human rights protection in Indonesia, Malaysia, Cambodia and Vietnam.